2003
DOI: 10.7326/0003-4819-139-7-200310070-00007
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences Pertaining to a Belief about Lung Cancer Surgery: Results of a Multicenter Survey

Abstract: Belief in accelerated tumor spread at surgery is prevalent among general pulmonary outpatients and lung cancer clinic patients facing lung surgery, particularly among African-American patients. Our findings may pertain to key racial disparities in lung cancer surgery and survival rates and suggest that culturally sensitive physician training or outreach programs directed at disparate beliefs and attitudes may help to address racial discrepancies in health care outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
154
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(159 citation statements)
references
References 23 publications
5
154
0
Order By: Relevance
“…25 It is likely that similar observations fueled popular 'myths' such as ''surgery provokes the tumor to spread'' that is reported by breast surgeons practicing in Africa, where the prognosis of breast cancer patients is particularly poor, 26 or as ''cancer spreads when the air hits it'' that is surprisingly widely held and believed in the U.S. by 61% of AA and 29% of CA individuals. 27 Although such folk beliefs likely contribute to delays in seeking treatment and poor prognosis, they may contain some truth regarding breast cancer progression that is now being uncovered by recent research, which supports a model for breast cancer clinical progression where primary tumor removal may accelerate the appearance of distant metastasis, mainly in premenopausal women. 28 According to this model, the clinical course of breast cancer is characterized by dormancy of subclinical metastases.…”
Section: Clinical Perspective: a Hierarchical Prognostic Modelmentioning
confidence: 99%
“…25 It is likely that similar observations fueled popular 'myths' such as ''surgery provokes the tumor to spread'' that is reported by breast surgeons practicing in Africa, where the prognosis of breast cancer patients is particularly poor, 26 or as ''cancer spreads when the air hits it'' that is surprisingly widely held and believed in the U.S. by 61% of AA and 29% of CA individuals. 27 Although such folk beliefs likely contribute to delays in seeking treatment and poor prognosis, they may contain some truth regarding breast cancer progression that is now being uncovered by recent research, which supports a model for breast cancer clinical progression where primary tumor removal may accelerate the appearance of distant metastasis, mainly in premenopausal women. 28 According to this model, the clinical course of breast cancer is characterized by dormancy of subclinical metastases.…”
Section: Clinical Perspective: a Hierarchical Prognostic Modelmentioning
confidence: 99%
“…I n their recent article, Gansler et al 1 discussed various myths held by those from low sociodemographic backgrounds and cited a study by Margolis et al 2 that stated that approximately 61% of African Americans and 29% of white Americans believe that lung cancer spreads when it makes contact with air. This is given as a reason for the relatively low compliance rate in screening and the reluctance to undergo cancer surgery noted among African Americans and, to a lesser extent, other underserved communities in the U.S. One can almost hear tongues clicking by reassuring physicians at the pity of misinformed people who forgo the life-saving benefits of the early detection of cancer because of cherished but wrong information.…”
Section: Sociodemographic Determinants Of Cancer Treatment Health Litmentioning
confidence: 99%
“…For example, Margolis et al reported that minority patients, most specifically AA patients, hold unique beliefs about lung cancer that may interfere with treatment seeking or adherence. 8 These limitations aside, the message of this well-articulated retrospective cohort study is an important one: that equalizing access to care may help in the national effort to improve quality of care for all patients irrespective of race/ethnicity, and to achieve equality of outcomes whenever feasible. With the implementation of the Patient Protection and Affordable Care Act, also known as Obamacare, many more Americans, including racial/ethnic minorities, are anticipated to gain greater access to health care and to treatments for serious conditions such as lung cancer.…”
mentioning
confidence: 99%